A study on preoperative clinico-radiological factors in predicting intraoperative difficulties in laparoscopic cholecystectomy - Goyal, Gourav; Patel, Rahul; Datey, Ashirvad (International Surgery Journal, 2025)
Background: Gallstones, or cholelithiasis, are common conditions causing patients to seek surgery. They can result from chronic or acute disorders in the biliary, pancreatic, gastrointestinal, and hepatic systems. The main pathways for gallstone formation are excessive bilirubin, cholesterol supersaturation, and impaired gall bladder contractility. Surgeons need to establish criteria for difficult laparoscopic cholecystectomy (LC) and conversion, but there’s no consensus among them. Methods: Observational analytical prospective cohort study, conducted in general surgery, People’s hospital, Bhopal from November 2022 to February 2024, patients diagnosed with cholelithiasis scheduled for LC in the study area during the study period. Results: LC is the gold standard treatment for symptomatic cholelithiasis. Preoperative prediction of conversion risk is crucial for planning surgery. Predicting difficult LC allows experienced surgeons to be present during surgery, preventing complications. Early decision-making can prevent unnecessary surgery prolongation. Despite attempts to develop scoring systems for difficult LC, they are complex, difficult to use in daily practice, and often cannot be applied preoperatively. Conclusions: LC is a common surgery for symptomatic cholecystectomy. A detailed clinical assessment and preoperative ultrasound are important to identify potential challenges and complications. Factors like recurrent acute cholecystitis, pancreatitis, chronic liver disease, and past hospitalizations can predict difficulties. Intraoperative issues may include bile spillage and bleeding. Difficult cases may require conversion to open surgery, extending operation time and hospital stays.